2022
DOI: 10.1038/s41598-022-15167-w
|View full text |Cite
|
Sign up to set email alerts
|

TCFL5 deficiency impairs the pachytene to diplotene transition during spermatogenesis in the mouse

Abstract: Spermatogenesis is a complex, multistep process during which spermatogonia give rise to spermatozoa. Transcription Factor Like 5 (TCFL5) is a transcription factor that has been described expressed during spermatogenesis. In order to decipher the role of TCFL5 during in vivo spermatogenesis, we generated two mouse models. Ubiquitous removal of TCFL5 generated by breeding TCFL5fl/fl with SOX2-Cre mice resulted in sterile males being unable to produce spermatozoa due to a dramatic alteration of the testis archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Consistent with the testis-specific expression of human Tcfl5 (Maruyama et al, 1998), two recent studies revealed TCFL5 is first expressed in mouse primary spermatocytes (Galán-Martínez et al, 2022;Xu et al, 2022). We used staged mouse testes (Nebel et al, 1961) to measure the abundance of Tcfl5 mRNA and protein across spermatogenesis.…”
Section: A-myb Is Expressed Before Tcfl5 During Male Meiosis Imentioning
confidence: 74%
“…Consistent with the testis-specific expression of human Tcfl5 (Maruyama et al, 1998), two recent studies revealed TCFL5 is first expressed in mouse primary spermatocytes (Galán-Martínez et al, 2022;Xu et al, 2022). We used staged mouse testes (Nebel et al, 1961) to measure the abundance of Tcfl5 mRNA and protein across spermatogenesis.…”
Section: A-myb Is Expressed Before Tcfl5 During Male Meiosis Imentioning
confidence: 74%
“…Of these sixteen TF candidates with PGC-enriched transcript expression, only seven (Gata2, Mga, Nr6a1, Tbx4, Tcfl5, Tfap2c, and Zfx) showed enriched expression in germ cells when compared to the somatic compartment of the gonad, and thus met our requirements for further in silico investigation (Supplementary Figure 9a). These candidate TFs have reported roles in cell fate determination, growth and fertility regulation, and meiotic progression 79,80 , all of which are in line with the cellular events that occur as PGCs commit to the female pathway. Nonetheless, the chromatin binding and gene expression of GATA2, MGA, TBX4, TCFL5, and TFAP2c showed the clearest patterns of sexual dimorphism in E13.5 PGCs and represented the most compelling TF candidates (Fig.…”
Section: A Computational Approach To Identify Candidate Tfs Regulatin...mentioning
confidence: 74%
“…Of these TFs, TCFL5 and TFAP2C showed the strongest enriched expression in XX PGCs. TCFL5 binds to the promoters of meiotic genes such as Sycp1 (synapsis) and Stag3 (cohesion) during spermatogenesis in the mouse 79 . Tcfl5 is indispensable for the completion of meiosis and spermatid maturation 79 , and meiosis of female germ cells 81 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the male meiotic prophase, developmental progression beyond the pachytene stage is a critical event in which multiple gene regulatory programs inactivate gene expression on sex chromosomes, suppress transposable elements, and progress toward the post-meiotic stage (Li et al 2013) (Sin et al 2015) (da Cruz et al 2016) (Ernst et al 2019). Accordingly, a subset of male germ cell-specific transcription factors is required for progression beyond the pachytene stage (Bolcun-Filas et al 2011) (Li et al 2013) (Oji et al 2020) (Horisawa-Takada et al 2021) (Oura et al 2021) (Xu et al 2022) (Galan-Martinez et al 2022) (Cecchini et al 2023). However, it remains unclear how pachytene progression is ensured in the male meiotic prophase and which transcription factors are responsible for this process.…”
Section: Introductionmentioning
confidence: 99%